Teatralny ekwiwalent literackiej autonarracji . Przypadek 'Kronosu' Krzysztofa Garbaczewskiego - Kowal, Justyna (Załącznik Kulturoznawczy, 2021)
The main assumption of the article is the interpretation of Kronos based on Witold Gombrowicz’s private journal, directed by Krzysztof Garbaczewski in Teatr Polski in Wrocław (2013). The author also seeks forms of transmitting and receiving relations in Gombrowicz’s diarism, (both in his Dziennik and Kronos) which are significant for performing arts and used in Garbaczewski’s staging. The director treated the structure of the writer’s intimate diary as a kind of creative method, attempting to translate the idea of self-narration into the language of theatre. The structure of Garbaczewski’s performance reflects the heterogeneous composition of Gombrowicz’s Kronos, despite treating its content only as a pretext. Garbaczewski’s staging can also be called an anti-spectacle, in which the vivid boundary between reality and mimicry, truth and confabulation, aesthetics and obscenum, a phenomenal and semiotic body is blurred.